Enantioselective chemoenzymatic synthesis of 2-arylpropionic acids and dihydropyrimidinones using lipases as biocatalysts - Alfaro Blasco, María (2011)
The enzymatic hydrolysis and racemization of alkyl 2-arylpropionates were investigated with respect to a possible dynamic kinetic resolution. Different enzymes were tested for the hydrolysis of several alkyl 2-phenylpropionates. Based on this screening, lipase B from Candida antarctica was chosen as the most active one. The use of this enzyme led to enantiomeric ratios of E = 12-13 for the hydrolysis of propyl rac-2-phenylpropionate in a two-phase system consisting of water and MTBE (1:1, (v/v)). Additionally, the racemization of the unreacted substrate alkyl 2-arylpropionates after enzymatic hydrolysis was then investigated and intensive studies were performed leading to a successful base-catalyzed racemization of these α-substituted propionates. The second part of this thesis consists of the development of an enantioselective process to synthesize the enantiomerically pure dihydropyrimidinone (S)-monastrol. When using lipase B from Candida antarctica a conversion of 52% and an enantioselectivity value of E = 13 were determined for the enzymatic hydrolysis of this O-acetylated monastrol in a reaction medium consisting of water and dichloromethane (4:1, (v/v)). Moreover, the influence of the alkyl chain on the enzymatic hydrolysis was studied and substrate O-butanoylated monastrol led to the best obtained results. A two step process was developed starting from this substrate rac-O-butanoylated monastrol for the synthesis of the desired product (S)-monastrol. The first step was based on a kinetic resolution catalyzed by Candida antarctica lipase B. Due to the (R)-selectivity of the enzyme the reaction was stopped at a conversion of 59% to afford a higher enantiomeric excess for the desired unreacted (S)-O-butanoylated monastrol. The enzymatic hydrolysis was carried out in a reaction media consisting of water and dichloromethane (4:1, (v/v)) and at 25°C. The product (R)-monastrol was obtained in 48% yield and with an enantiomeric excess of 66% ee. The unreacted substrate (S)-O-butanoylated monastrol was isolated ...